X-ray fluorescence analysis using a standardless method - Martins, Luís de Souto (2020)
Energy Dispersive X-ray Fluorescence spectrometry (EDXRF) is a non-destructive analytical technique that allows multi-element analysis of a large variety of materials in a relatively fast and simple way, and is used in a broad range of areas. This technique resorts to calibrated standard samples for each type of sample to be analysed, as well as the knowledge of Fundamental Parameters (FP). The use of standards have several drawbacks to consider such as the unavailability of standards for certain types of materials, the associated monetary costs, and inaccuracy of the standard’s measurements. On the other hand, the inaccuracy of Fundamental Parameters limits the accuracy of the quantification. Furthermore, FP used by quantification software are included in built-in tabulation inaccessible to the user. EDXRF spectrometers employed in triaxial geometry allow the experimental measurement of the Rayleigh-to-Compton scattering intensity ratio. The measurement of these ratios of standard samples permits a method for determination of the average atomic number Zavg of unknown samples. In this work, using the Geant4 toolkit, a code is implemented to simulate the X-ray spectrum obtained from employing a triaxial geometry spectrometer, aiming for both elemental quantification from the characteristic peaks and the determination of Compton-to-Rayleigh scattering ratio. Simulation results are compared with experimental measurements of standard reference materials, showing a good agreement for the simulated peak intensities, as well as for the simulated scattering ratios. Zn K-shell FP are calculated using the multiconfiguration Dirac-Fock approach, presenting good agreement when comparing with the available values in literature. A comparison of K-shell fluorescence yield and partial fluorescence yield values is presented, regarding different references from which a comprehensive set of values can be used for atomic relaxation libraries. These comparisons point that further studies should be employed before changing Geant4 library for atomic relaxation.